2003
DOI: 10.1002/anie.200352393
|View full text |Cite
|
Sign up to set email alerts
|

Site Titration with Organic Bases During Catalysis: Selectivity Modifier and Structural Probe in Methanol Oxidation on Keggin Clusters

Abstract: Catalytic reactions often require several types of sites with distinct functions, and the relative abundance of these sites influences the rate and selectivity of desired reactions. Heteropolyacid clusters with Keggin structures, which contain acid and redox functions, [1,2] have recently emerged as interesting catalysts for organic reactions involving bifunctional pathways.We recently discovered a selective one-step synthesis of dimethoxymethane (CH 3 OCH 2 OCH 3 , DMM, methylal) by oxidation of methanol at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…4 shows the reaction pathway for selective conversion of methanol to DMM over bifunctional oxidation and acid catalyst. It is known that formaldehyde (FA) is produced by oxidation catalysis of HPA, while dimethyl ether (DME) is produced by acid catalysis of HPA in the primary reaction of methanol [10][11][12]. In the secondary reaction, dimethoxymethane (DMM) is produced via acidcatalyzed reaction of methoxymethanol (MM) intermediate with methanol.…”
Section: Fig 2 (A) Xps Spectrum Of N-mc Support and (B) Deconvolutementioning
confidence: 99%
See 3 more Smart Citations
“…4 shows the reaction pathway for selective conversion of methanol to DMM over bifunctional oxidation and acid catalyst. It is known that formaldehyde (FA) is produced by oxidation catalysis of HPA, while dimethyl ether (DME) is produced by acid catalysis of HPA in the primary reaction of methanol [10][11][12]. In the secondary reaction, dimethoxymethane (DMM) is produced via acidcatalyzed reaction of methoxymethanol (MM) intermediate with methanol.…”
Section: Fig 2 (A) Xps Spectrum Of N-mc Support and (B) Deconvolutementioning
confidence: 99%
“…produced via consecutive bifunctional oxidation-acid-oxidation catalysis [10][11][12]. This implies that both well-controlled oxidation and acid catalytic functions are required for the selective conversion of methanol to DMM.…”
Section: May 2009mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the selective oxidation of methanol to DMM might involve two steps: (1) oxidation of methanol to formaldehyde on redox sites and (2) condensation of formaldehyde produced with additional methanol to DMM on acidic sites. Thus, the strengths of surface acidity and redox ability of a catalyst were two important aspects in determining the selective oxidation of methanol to DMM [36][37][38][39][40].…”
Section: Selective Oxidation Of Methanol To Dimethoxymethanementioning
confidence: 99%